Тваринництво на античному поселенні Аджигол-І - Журавльов, О.П.; Яковенко, В.І. (Археологія, 1997)
У статті на підставі остеологічних матеріалів подано характеристику свійських тварин і тваринництва загалом на античному поселенні Аджигол-І. Проведенные исследования остеологического материала, найденного при археологических раскопках античного поселения Аджигол-І (Николаевская область, Очаковский район), позволили сделать выводы об отсутствии сезонности забоя домашних животных, наличии хорошей кормовой базы в районе поселения и оседлом способе ведения хозяйства жителями данного поселения. The studies of the osteological findings carried out during archaeological excavations of antique settlement Adzhigol-I (the Nikolaev Region, Ochakov district) have permitted conclusions to be made on the absence of the seasonal character in the slaughter of domestic animals, presence of appropriate food base in the settlement and settled way of farming of inhabitants of that settlement.